GUIDED PROJECT BASED LEARNING (PJBL) ASSITED WITH DAMAR KURUNG VISUAO LEARNING MEDIA INTO INCREASE ACTIVE LEARNING - Nur Indah Rahmawati; Masruroh; Dhiah Fitrayati (JEES: Journal of Economic Empowerment Strategy, 2023)
The application of learning that favors students is still constrained by the dominance of the teacher in using the lecture method and the lack of use of learning media. This has an effect on the learning activity of students which decreases. One of the ways to increase students' active learning is to apply a guided Project Based Learning (PjBL) model. This research is a Classroom Action Research using a one-group pretest posttest design. The technique used to collect data is observation with the observation sheet instrument and student learning outcomes. The research was conducted at SMA Negeri 1 Cerme. The sample of this research was students of class X-12, totaling 35 people. The results of this study indicate that the learning activeness of students has increased learning from pre-cycle to cycle I, from cycle I to cycle II.